Environmental Oriented Problem-Based Learning (PBL) Improves Learning Outcomes and Self-Efficacy of Students In Social Studies In Fifth-Grade Elementary Schools - Arisanti, Dewa Ayu Kade; Dantes, Nyoman; Suastika, I Nengah (Universitas Pendidikan Ganesha, 2022)
The lack of teacher abilities and skills in varying the application of learning models impacts low learning outcomes and student self-efficacy in social studies subjects in grade V. This study aims to produce a product in the form of an environment-oriented problem-based learning model. This research belongs to the type of development research that was developed using the 4D model. The 4D model consists of four research stages: defining, designing, developing, and deploying. The subjects involved in this study were social studies learning experts, expert practitioners of 15 high-grade teachers, and 51 fifth-grade elementary school students. Data collection in the study was carried out using non-test and test methods, with research instruments in the form of questionnaires and multiple-choice tests. The data obtained in the study were then analyzed using a feasibility test with validity and product trials. The research analysis results show that the learning model developed gets an average score of 4.9 in the